Atlas of stress-strain curves. (ASM International, 2002)
Annotation Contains more than 1400 curves, almost three times as many as in the 1987 edition. The curves are normalized in appearance to aid making comparisons among materials. All diagrams include metric units, and many also include U.S. customary units.
Keywords: Stress-strain curves -- Atlases.; Metals -- Testing.; elektronické knihy; electronic books